Tefsir ve Tasavvuf Kaynaklarında Vahyin Keyfiyeti ve Devamlılığı Hususundaki Tartışmalar - Küçük, Ahmet; Hanif, Mohammd Ajmal (Fırat University, 2022)
Bu çalışmamız vahyin keyfiyeti ve kesilip kesilmediği hususunu içermektedir. Bu konuda öteden beri mutasavvıflar ve müfessirlerin da dâhil olduğu diğer ulema arasında ciddi görüş ayrılıkların olduğu bilinen bir gerçektir. Bu farklılıklar her ne kadar son dönem tasavvufunda iyice gün ışığına çıktıysa kökleri ilk dönemlere kadar geriye gitmektedir. Sözlük anlamında vahyin bir türü olaraksayılabilen ilhamın (ilham ile birlikte sadık rüyalar da lugat anlamında vahiy sayılabilir) terim olarak da vahyin kapsamında değerlendirilip değerlendirilmemesi, dini meselelerde bağlayıcılık arz edip etmemesi hususları hep tartışıla gelmiştir. Tefsir ve Tasavvuf Kaynaklarında Vahyin Keyfiyeti ve Devamlılığı Hususundaki Tartışmalar adlı bu makalemizde örnekleme metoduyla klasik ve modern dönem tefsir kaynaklarıyla tasavvuf disiplinin ana kaynakları esas alınarak farklılıklar ve benzerlikler tespit edilmeye çalışılacaktır. Bu doğrultuda gerek tefsir ve tasavvuf disiplinindeki vahye ve vahyin devamı iddia olduğu edilen ilhama yönelik farklı yaklaşımlar gerekse müfessirlerin ve mutasavvıfların kendi aralarındaki görüş ve yöntem farklılıkları eleştirel bir bakış açısıyla değerlendirmeye tabi tutularak mukayese edilecektir.

Divine revelation (wa?y), as a Qur'anic and religious concept in exegetical sources, isusually mentioned together with the institution of Prophethood (nubuwwa). Revelation came to itsend with the end of Prophethood. Therefore, although some have evaluated inspiration (ilh?m) andtrue dream (ru?y? s?diqa) within the this context of revelation, according to most of Islamic scholars,it is not permissible to refer to the recevings of the divinely saints as revelation. Revelation, for whichthe holy Qur'an designates three pattern of descension, is discussed also in three categoriesthroughout the history of Islamic intellectual thought. Scholars of tafsir and theologians,philosophers, and mystics, all hold and bolster different views on the nature of revelation. Claims inSufi literature that inspiration can descend to divinely saints -beyond immediate delivery to theheart- through direct or indirect divine communication from behind a veil and through angles can beevaluated as an effort to create a conception of revelation that corresponds to the three modes ofrevelation, adressed in Qur’an, peculiar to prophets. With regard to the issue of continuity of divine revelation, a thorough examination of the Sufiliterature leads to the conclusion that revelation continues to decsend in its verbal form asinspiration but also, according to some Sufi authorities, in its noun forms unaniously considered aspeculiar to the prophets. Therefore, especially since the period of Sufism’s intermingling withphilosophy, the issues of accommdating sainthood (wal?ya) within the framework of generalprophethood (nubuwwa ??mme), the distinction between revelation and inspiration and itscontinuity appear as a very complex, unframed and unlimited field. This can be observed in theinstances addressed in this study.
Discussions on Forms and Continuity of Divine Revelation in Tafsir and Sufi Literature
Keywords: Religious Studies; Din Araştırmaları